2005
DOI: 10.1097/01.alc.0000150015.84381.63
|View full text |Cite
|
Sign up to set email alerts
|

Drinking, Alcohol Problems and the Five-Year Recurrence and Incidence of Male to Female and Female to Male Partner Violence

Abstract: Background: This study examined the 5-year incidence and recurrence of male to female (MFPV) and female to male partner violence (FMPV) as well as their relationship with drinking and alcohol problems among intact couples in the United States.Methods: A national sample of couples 18 years of age or older were interviewed in 1995 and again in 2000.Results: Recurrence is slightly higher for FMPV (44%) than MFPV (39%), whereas incidence rates are similar for these two types of violence (MFPV, 5.7%; FMPV, 6%). Cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
85
1
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(90 citation statements)
references
References 32 publications
2
85
1
2
Order By: Relevance
“…A certain number of victims had a history of chronic alcohol and/or illegal drug abuse (6.5%) and had consumed before the homicide: 16.7% and 6.5%, respectively, presented positive blood alcohol and illegal drugs concentration, which is far below the rates referred in other studies 9,18,27 but also compared to the prevalence of lifetime alcohol abuse considering the …”
Section: Victims and Perpetratorsmentioning
confidence: 65%
“…A certain number of victims had a history of chronic alcohol and/or illegal drug abuse (6.5%) and had consumed before the homicide: 16.7% and 6.5%, respectively, presented positive blood alcohol and illegal drugs concentration, which is far below the rates referred in other studies 9,18,27 but also compared to the prevalence of lifetime alcohol abuse considering the …”
Section: Victims and Perpetratorsmentioning
confidence: 65%
“…This study extends previous research in several ways. Previous research in college populations has focused primarily on the relationship between IPV and alcohol consumption, despite the fact that alcohol-related problems have been associated with IPV perpetration in other populations (Caetano et al, 2005;White and Chen, 2002;White and Widom, 2003). In addition, previous research has primarily focused on alcohol expectancies as a potential moderator of the relationship between IPV and drinking.…”
Section: Discussionmentioning
confidence: 99%
“…Based on studies of the general population (e.g., Caetano et al, 2005), as well as research with clinical populations (e.g., Fals-Stewart et al, 2005), alcohol consumption has been associated with the perpetration of IPV. Similarly, much of the existing literature on alcohol consumption and IPV perpetration in college populations points to a positive relationship between the two behaviors (Nicholson et al, 1998;Shook et al, 2000;Williams and Smith, 1994), where the use of alcohol before or during a relationship conflict is associated with greater IPV.…”
Section: Intimate Partner Violence Perpetration and Alcohol Consumptionmentioning
confidence: 99%
“…3 By estimating the association between the amount of alcohol consumed and IPV episodes, a recent study revealed that all perpetrations of male violence against women and of women against men increase significantly with a frequency of consumption of five or more drinks per episode. 6 In general, during IPV episodes, men had consumed alcohol between 6% and 57% of episodes and women between 10% and 27% of episodes, according to results from another study. 21 Despite strong scientific evidence that alcohol consumption is associated with higher risk of IPV, there were no national population studies in Brazil that have investigated this association until now.…”
Section: Introductionmentioning
confidence: 92%